PERBANDINGAN FONEM BAHASA MELAYU RIAU ISOLEK KELARIK DENGAN ISOLEK SEDANAU - Romiyati Romiyati; Auzar Auzar; Hermandra Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is titled Comparison of Malay Language Foneme Riau Isolek Kelarik with Isolek Sedanau. This study aims to describe different or not vocal phonemes between isolated Kelarik with Isolek Sedanau. Describe different or not consonant phonemes between isolated Kelarik with Isolek Sedanau. Describe different or not diphthong phoneme between isolate Kelarik with Isolek Sedanau. Describe the realization of vocal phonemes of Malay isolate Kelarik dan Sedanau. Describe the realization of consonant phonemes of Malay language isolek Kelarik dan Sedanau Describe the realization of phoneme diftong Malay isolek Kelarik dan Sedanau. Data collection techniques by observation, recording, and recording on public utterances Kelarik and Sedanau with the amount of 88 data. To obtain the results of research data, the author mentraskip results, recording, and recording of the pronunciation community Kelarik and Sedanau. To get the result of phoneme comparison form found in Riau Malay language between isolek Kelarik with isolasi Sedanau writer clarify comparison of phonemes contained in Riau Malay language between isolek Kelarik with dialect Sedanau. Further analyzed, the comparison of phonemes contained in the Riau Malay language between isolarik Kelarik with isolan Sedanau. Based on the theory used. Based on the result of research, it is found that (1) there is no difference of vowel phonemes on Malay Isolek Kelarik and Sedanau; (2) there is no difference of consonant phoneme in Malay Isolek Kelarik dan Sedanau; (3) there is difference of diphthong phonemes in Melayu Kelarik language with Sedanau.Keywords: comparison, phoneme, Malay language, isolek.